Comparison of DNA extraction methods for COVID-19 host genetics studies. - Ronaldo Celerino da Silva; Suelen Cristina de Lima; Wendell Palôma Maria Dos Santos Reis; Jurandy Júnior Ferraz de Magalhães; Ronaldo Nascimento de Oliveira Magalhães; Brijesh Rathi; Alain Kohl; Marcos André Cavalcanti Bezerra; Lindomar Pena (PLoS ONE)
The coronavirus disease 2019 (COVID-19) pandemic has resulted in global shortages in supplies for diagnostic tests, especially in the developing world. Risk factors for COVID-19 severity include pre-existing comorbidities, older age and male sex, but other variables are likely play a role in disease outcome. There is indeed increasing evidence that supports the role of host genetics in the predisposition to COVID-19 outcomes. The identification of genetic factors associated with the course of SARS-CoV-2 infections relies on DNA extraction methods. This study compared three DNA extraction methods (Chelex®100 resin, phenol-chloroform and the QIAamp DNA extraction kit) for COVID-19 host genetic studies using nasopharyngeal samples from patients. The methods were compared regarding number of required steps for execution, sample handling time, quality and quantity of the extracted material and application in genetic studies. The Chelex®100 method was found to be cheapest (33 and 13 times cheaper than the commercial kit and phenol-chloroform, respectively), give the highest DNA yield (306 and 69 times higher than the commercial kit and phenol-chloroform, respectively), with the least handling steps while providing adequate DNA quality for downstream applications. Together, our results show that the Chelex®100 resin is an inexpensive, safe, simple, fast, and suitable method for DNA extraction of nasopharyngeal samples from COVID-19 patients for genetics studies. This is particularly relevant in developing countries where cost and handling are critical steps in material processing.